Eksistensi Ulama Dayah Dalam Perpolitikan di Aceh Tahun 2024 - Novriansyah, Muhammad; Zuriah, Zuriah; Saputra, Teuku Amnar (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2024)
From time to time, the role of Ulama in Indonesia has been very important in its position, as well as in Aceh as a region that upholds Islamic law. The role of Ulama is not only limited to educators and lecturers in mosque pulpits, but historically they have also been very influential in the resistance against colonialism. After MOU Helsingki between Indonesia and the Free Aceh Movement (GAM), many local parties emerged in political contestation, one of which was a party dominated by ulama. The role of ulama, who are basically educators, is starting to exist in the world of politics. This research aims to determine the existence of Ulama Dayah in politics in Aceh, as well as to determine the role of Ulama Dayah in politics in Aceh. This research is qualitative research with a phenomenological approach. Data collection techniques were carried out using participant observation and documentation. The results of the research show that Ulama Dayah are increasingly present in politics in Aceh, especially seen from the existence of new parties that are clearly affiliated with Ulama Dayah. Then, looking at the role of the Ulama in Aceh from time to time, they have played many roles in society apart from being educators. Ulama play an active and passive role in political contestation in Aceh.